Transcranial Doppler Ultrasonography of the Basilar Artery in Cerebral Small Vessel Disease - Vikarenko, M. (Journal of Education, Health and Sport, 2025)
This study evaluates the diagnostic value of transcranial Doppler ultrasonography (TCD) of the basilar artery in patients with cerebral small vessel disease (CSVD). TCD, specifically via the transforaminal (suboccipital) approach, is a non-invasive method to assess cerebral hemodynamics, particularly in the posterior circulation. Although it cannot directly visualize small vessels due to limited spatial resolution, it can detect indirect indicators of microvascular dysfunction—most notably elevated pulsatility index (PI) and reduced end-diastolic velocity (EDV), both of which suggest increased distal resistance and impaired perfusion. A clinical study involving 84 patients with CSVD (verified by STRIVE criteria) found that the mean PI was significantly elevated (1.6±0.1), while EDV and mean flow velocity (MFV) were decreased, reflecting posterior hypoperfusion. No macroangiopathy (e.g., stenosis, turbulent flow) was observed. In patients with accessible temporal windows, additional TCD via the transtemporal approach revealed similar findings, reinforcing the transforaminal method’s utility when the temporal bone window is closed—common in elderly patients. The method demonstrated 76.9% sensitivity and 81.3% specificity for detecting indirect signs of CSVD. Though operator-dependent and non-specific in differentiating from other pathologies, transforaminal TCD offers practical advantages: it is non-invasive, suitable for repeated use, and valuable when MRI is unavailable. It is most effective when integrated into a multimodal diagnostic approach, including clinical evaluation and neuroimaging. Conclusion: Transforaminal TCD is a clinically promising and sufficiently accurate tool for assessing cerebral hemodynamics in CSVD, especially for identifying increased cerebrovascular resistance and impaired posterior perfusion.